Karakteristik Bubuk Biji Buah Salak Bali : Kajian Suhu dan Waktu Penyangraian - Pratama Putra, I Gusti Ngurah; Wrasiati, Luh Putu; Wartini, Ni Made (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 9 No 2 (2024)DO - 10.24843/JITPA/2024.v09.i02.p05, 2025)
The purpose of this study are to find out the physico-chemical and sensory characteristics of Sallaca edulis seeds’s powder with various roasting temperatures (190 ± 2 o C, 200 ± 2 o C and 210 ± 2 o C) and roasting time (10 minutes, 20 minutes and 30 minutes) as well as identifying the flavour compounds contained in the Sallaca edulis seeds’s powder. Group randomized design was used in this study. The observed variables include water content, ash content, water soluble cider content, tannin content, phenol content, trio duo test, scoring test against parameters of taste, color, aroma, hedonic test againts taste, color, aroma, color intensity test and identification of flavor compounds. Data analyzed with Analysis of Variance (ANOVA) and continued with the duncan test. The results showed that roasting temperature and roasting time give a real influence, but the interaction between these two treatments has no real effect (P<0.05). The roasting treatment at 210 o C and roasting time for 10 minutes is the best treatment according to the highest panelist preference with water content about 3.68 %, ash content about 3.34 %, caffeine content about 0.0145 %, tannin content about 5.07 g/100g, total phenol about 20.07 mg/100g and water soluble essence about 13.51 %. There are several volatile compounds that identified with similarity levels above 90% . There are palmitic acid with  93% similarity rate at 15,136 minutes retention time, linoleate acid with 96% similarity rate at 16,993 minutes retention time and (tetrahydroxyclopentadienone) tricarbonyliron with 93 % similarity rate at 17,197 minutes retention time.